2021
DOI: 10.3389/fimmu.2021.736030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Exosome-Related Gene Risk Model to Evaluate the Tumor Immune Microenvironment and Predict Prognosis in Triple-Negative Breast Cancer

Abstract: BackgroundAs a kind of small membrane vesicles, exosomes are secreted by most cell types from multivesicular endosomes, including tumor cells. The relationship between exosomes and immune response plays a vital role in the occurrence and development of tumors. Nevertheless, the interaction between exosomes and the microenvironment of tumors remains unclear. Therefore, we set out to study the influence of exosomes on the triple-negative breast cancer (TNBC) microenvironment.MethodOne hundred twenty-one exosome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Different immune infiltrations can lead to different outcomes in tumors (43,44). For example, activated CD4 + memory T cell infiltration has been shown to be associated with poor prognosis and immune therapy response in several cancers (45,46), as have activated mast cells (47)(48)(49). This indicates that SLC2A1 might play a vital role in regulating the tumor immune microenvironment, and affects the prognosis of tumors by regulating infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Different immune infiltrations can lead to different outcomes in tumors (43,44). For example, activated CD4 + memory T cell infiltration has been shown to be associated with poor prognosis and immune therapy response in several cancers (45,46), as have activated mast cells (47)(48)(49). This indicates that SLC2A1 might play a vital role in regulating the tumor immune microenvironment, and affects the prognosis of tumors by regulating infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study also revealed that CXCL10 is highly expressed in pCR patients, indicating that a higher expression level of CXCL10 may result in pCR in BC patients. Several studies have shown that CXCL11, CXCL13, and CXCL14 biomarkers are closely related to chemotherapeutic resistance in BC (29)(30)(31)(32)(33). ESR1 encodes estrogen receptor α (ERα) and plays an important role in the tumorigenesis of BC (34).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, anti-tumor immunotherapy is attracting more and more attention in BC. Biomarker-driven therapies and immune checkpoint inhibitors are proving to be promising options for TNBC treatments ( 4 , 5 ). However, drug resistance in tumors is still a problem that cannot be ignored in TNBC treatment.…”
Section: Introductionmentioning
confidence: 99%